Autophagy Regulation on Pyroptosis: Mechanism and Medical Implication in Sepsis - Ran Guo; Hao Wang; Na Cui (Mediators of Inflammation)
Sepsis is defined as a life-threatening disease involving multiple organ dysfunction caused by dysregulated host responses to infection. To date, sepsis remains a dominant cause of death among critically ill patients. Pyroptosis is a unique form of programmed cell death mediated by the gasdermin family of proteins and causes lytic cell death and release of proinflammatory cytokines. Although there might be some positive aspects to pyroptosis, it is regarded as harmful during sepsis and needs to be restricted. Autophagy was originally characterized as a homeostasis-maintaining mechanism in living cells. In the past decade, its function in negatively modulating pyroptosis and inflammation during sepsis has attracted increased attention. Here, we present a comprehensive review of the regulatory effect of autophagy on pyroptosis during sepsis, including the latest advances in our understanding of the mechanism and signaling pathways involved, as well as the potential therapeutic application in sepsis.